Knowledge and Attitude of Adolescents about Unwanted Pregnancy in SMA Negeri 8 Kupang - Dewa Ayu Ratna Ningrum; Masrida Sinaga; Amelya Sir (Lontar : Journal of Community Health, 2022)
Unwanted pregnancy in adolescents is related to reproductive health behavior, including knowledge, attitudes, and actions. Knowledge will produce positive or negative attitudes, and from these attitudes, individuals will apply them in the form of actions, including sexual behavior. This study described adolescent knowledge and attitudes about unwanted pregnancy. The research method used in this study was descriptive with a quantitative approach. The study was conducted at SMA Negeri 8 in March-April 2021. Teenage girls in grades X and XI of SMAN 8 Kupang were used in this study totaling 323 people. The sample used was 179 people taken by a simple random sampling technique and the Slovin formula. Data was collected using an online questionnaire. The results showed that most respondents had good knowledge about unwanted pregnancy and had a positive attitude towards unwanted pregnancy. Schools should be more selective in receiving and providing information on sexual behavior before marriage and unhealthy dating relationships for students. At the same time, the Kupang City Education Department suggested launching a new policy related to reproductive health education for adolescents. Keywords: adolescent, attitude, knowledge, unwanted pregnancy